1997
DOI: 10.1023/a:1024818110678
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of sexual harassment: The effects of gender, legal standard, and ambivalent sexism.

Abstract: This research tests the possibility that the reasonable woman as compared to the reasonable person test of hostile work environment sexual harassment interacts with hostile and benevolent sexist beliefs and under some conditions triggers protectionist attitudes toward women who complain of sexual harassment, We administered to a sample of undergraduates the ambivalent sexism inventory along with the fact patterns in two harassment cases and asked them to make legally relevant decisions under either the reasona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
128
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(141 citation statements)
references
References 39 publications
11
128
2
Order By: Relevance
“…These actions are instrumental to the individual in creating a disparaging and humiliating climate for female workers who are perceived to violate traditional gender ideals and encroach on male territory (e.g., by being seen to take on a man's job). Moreover, our findings support extant research reporting that males high (versus low) in HS evaluate ambiguous social-sexual misconduct as less indicative of hostile work environment harassment (Wiener & Hurt, 2000;Wiener et al, 1997;Wiener et al, 2010). As BS encompasses attitudes toward women that are subjectively positive in tone and comparatively more chivalrous (albeit sexist in terms of viewing women in restricted social and economic roles) than HS, it is understandable that BS should correlate with the MDiSH at a smaller magnitude or indeed be unrelated.…”
Section: The Mdish and Impression Management (Im)supporting
confidence: 78%
See 1 more Smart Citation
“…These actions are instrumental to the individual in creating a disparaging and humiliating climate for female workers who are perceived to violate traditional gender ideals and encroach on male territory (e.g., by being seen to take on a man's job). Moreover, our findings support extant research reporting that males high (versus low) in HS evaluate ambiguous social-sexual misconduct as less indicative of hostile work environment harassment (Wiener & Hurt, 2000;Wiener et al, 1997;Wiener et al, 2010). As BS encompasses attitudes toward women that are subjectively positive in tone and comparatively more chivalrous (albeit sexist in terms of viewing women in restricted social and economic roles) than HS, it is understandable that BS should correlate with the MDiSH at a smaller magnitude or indeed be unrelated.…”
Section: The Mdish and Impression Management (Im)supporting
confidence: 78%
“…Studies consistently document that men who are higher in HS (but not BS) evaluate ambiguous social-sexual misconduct as less indicative of hostile work environment harassment when using the "reasonable person" legal standard (see Wiener & Hurt, 2000;Wiener, Hurt, Russell, Mannen, & Gasper, 1997;Wiener et al, 2010). It has also been reported that HS (but not BS) positively predicts greater tolerance of sexual harassment (Russell & Trigg, 2004).…”
Section: Assessing Convergent and Discriminant Validity Of The Mdishmentioning
confidence: 99%
“…The men's higher scores in HS and BS confirm the results obtained in other studies (Feather, 2004;Feather & Boeckmann, 2007;Forbes et al 2004;Forbes et al 2007;Fowers & Fowers, 2010;Garaigordobil & Aliri, 2011a, 2011bGlick & Fiske, 1996;Glick et al 1997;Lameiras & Rodríguez, 2003;Lameiras et al 2007;Lee et al 2007;Liang, 2007;Masser y Abrams, 1999;Pozo et al 2010;Russel & Trigg, 2004;Travaglia et al 2009;Viki et al 2003;Wiener & Hurt, 2000;Wiener et al 1997). However, other investigations did not find gender differences in BS (Chen et al 2009;Eastwick et al 2006;Expósito et al 1998;Lameiras & Rodríguez, 2002;Lameiras et al 2006;Pereira et al 2005;Sakalli-Ugurlu, 2010;Sakalli-Ugurlu et al 2007;Tasdemir & Sakalli-Ugurlu, 2010;Vaamonde, 2010).…”
Section: Discussionsupporting
confidence: 81%
“…Some studies have reported that men score significantly higher in HS and BS (Feather, 2004;Feather & Boeckmann, 2007;Forbes, Adams-Curtis & White, 2004;Forbes, Collinsworth, Jobe, Braun & Wise, 2007;Fowers & Fowers, 2010;Garaigordobil & Aliri, 2011a, 2011bGlick & Fiske, 1996;Glick, Diebold, Bailey-Werner & Zhu, 1997;Lameiras & Rodríguez, 2003;Lameiras, Rodríguez, Calado, Foltz & Carrera, 2007;Lee, Pratto & Li, 2007;Liang, 2007;Masser & Abrams, 1999;Pozo, Martos & Alonso, 2010;Russel & Trigg, 2004;Travaglia, Overall & Sibley, 2009;Viki, Abrams & Hutchison, 2003;Wiener & Hurt, 2000;Wiener, Hurt, Russell, Mannen & Gasper, 1997). However, other investigations found no gender differences in BS (Chen, Fiske & Lee, 2009;Eastwick et al 2006;Expósito, Moya & Glick, 1998;Garaigordobil & Aliri, 2012;Glick, Sakalli-Ugurlu, Ferreira & Aguiar de Souza, 2002;Lameiras & Rodríguez, 2002;Lameiras, Rodríguez, Calado, Foltz & González, 2006;Pereira, Gouveia, da Silva & Marques, 2005;Sakalli-Ugurlu, 2010;Sakalli-Ugurlu, Sila Yalcin & Glick, 2007;Tasdemir & Sakalli-Ugurlu, 2010;Vaamonde, 2010), or else they found higher scores in men but only up to the age of 42 years (Lameiras, Rodríguez & González, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…To date, researchers have examined how jurors make liability decisions in sexual harassment cases (Gutek et al, 1999;Kovera, McAuliff, & Hebert, 1999;Wiener, Hurt, Russell, Mannen, & Gasper, 1997;Wiener, Watts, Goldkamp, & Gasper, 1995) but have ignored what happens after jurors find a defendant liable (Kovera & Cass, 2002). …”
mentioning
confidence: 99%